Corrosion protection of 316L stainless steel by (PVDF/HA) composite coating using a spinning coating technique - Asra Ali Hussein; Nawal Mohammed Dawood; Ammar Emad Al-kawaz (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2021)
Polymer coatings are increasingly used in varied fields and applications from simple coatings of barrier to intricated nanotechnology based composite. In the present study, polyvinylidene fluoride(PVDF)/Hydroxyapatite (HA )coatings were produced by spin coating technique over 316L SS. Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM) were used to observe the coated 316L SS substrates surface morphology. The corrosion protection efficiency of pure polyvinylidene fluoride and polyvinylidene fluoride/HA nanocomposite coatings on 316L SS was inspected using potentiodynamic polarization along with the ions release techniques in Hank’s solution. A superior biocompatibility and an improved protection performance against corrosion were obtained for the 316L SS samples with nanocomposite coatings compared with the pure polyvinylidene fluoride coatings and pristine 316L SS counterparts. The 316L SS samples coated by PVDF/HA nanocomposite showed enhanced corrosion protection within Hank’s solution. The corrosion of 316L SS samples within Hank’s solution increased from 92.99% to 99.99% when using 3wt% HA due to increasing the PVDF inhibition efficiency. Good agreements in the electrochemical corrosion parameters were obtained from using ions release and potentiodynamic polarization tests.